Understanding Narrative - Gerald Prince (Studies in 20th & 21st Century Literature, 1981)
Our ability to understand narratives—that is, our capacity for retelling them, paraphrasing them, summarizing them, expanding them, and specifying (at least some of) their points—is a function of our narrative competence. The latter is shown to include the following set of knowledges and abilities: (1) the knowledge that narrative consists of narrating (signs representing the narrating activity, its origin, and its destination) and narrated (signs representing real or fictive situations and events in a time sequence) and the ability to distinguish between the two; (2) the knowledge that the narrated describes changes of situations in time and that the preservation of its main chronological features is important for the preservation of its meaning; (3) the ability to focus on the narrating and, more particularly, on those evaluative statements pointing to a narrative lesson; (4) the ability to process the narrated in terms of a contrastive analysis; and (5) the ability to generalize the particulars depicted in the world of the narrated.
Keywords: narrative; narrative competence; knowledge; signs; narrating; origin; destination; time sequence; preservation of meaning; meaning; contrastive analysis; generalization; symbol